2019
DOI: 10.1108/edi-01-2019-0040
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the situation and person-based predictors of work–family conflict among married working professionals in India

Abstract: Purpose The purpose of this paper is to ascertain the situation (presence of young children, working hours, social and organizational support) and person-based factors (core self-evaluations) that influence work-family conflict (both work-to-family conflict (WFC) and family-to-work conflict (FWC)) and to examine the relative power of situational factors vs person-based factors in predicting work-family conflict. Design/methodology/approach Data were collected from 367 married working professionals from eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 74 publications
1
30
0
Order By: Relevance
“…With regards to spouse, a spouse’s personality, attitudes and characteristics influence the other spouse (Eby et al, 2005; Everding, 2014). Baral (2019) found that spouse’s personality accounted for more variance in family-to-work conflict than in work-to-family conflict. Further, some researchers suggest that big five personality model has potential implications on how couples experience WFC (Eby et al, 2005; Everding, 2014; Kailasapathy et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…With regards to spouse, a spouse’s personality, attitudes and characteristics influence the other spouse (Eby et al, 2005; Everding, 2014). Baral (2019) found that spouse’s personality accounted for more variance in family-to-work conflict than in work-to-family conflict. Further, some researchers suggest that big five personality model has potential implications on how couples experience WFC (Eby et al, 2005; Everding, 2014; Kailasapathy et al, 2014).…”
Section: Introductionmentioning
confidence: 95%
“…Due to the mix of traditional and modern socio-cultural aspects in the South Asian context, employees show significant differences in the way they involve themselves in work and family roles (Akkas et al, 2015; Baral, 2019; Kailasapathy et al, 2014). Further, Rajadhyaksha and Bhatnagar (2000) found that salience given towards marital and parental roles by Indian dual-earner couples varied across the life cycle but there was no reversal in salience towards work and family roles of men and women after midlife.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations